Smart Local Wisdom Finance: Culturally Based Financial Literacy Innovation to Increase the Competitiveness and Sustainability of MSMEs in Parepare City - Ar, Andi; Arfianty, Arfianty (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) in Parepare City, integrate the values ​​of local wisdom of pangadereng into financial management practices, and design a Smart Local Wisdom Finance model based on culture and digital technology. The study used a mixed methods approach with an explanatory sequential design. Quantitative data were obtained through a survey of 100 active MSMEs, while qualitative data were collected through in-depth interviews, observations, and Focus Group Discussions (FGDs). The results showed that the level of financial literacy of MSMEs was in the low-moderate category. 68% of respondents had not separated personal and business finances, 74% had not prepared cash flow reports, and 58% had not accessed formal financing. The results of the linear regression showed that financial literacy had a positive and significant effect on MSME performance with a coefficient of 0.648 and an R² value of 0.42. The integration of the values ​​of lempu', ade', bicara, and resopa strengthens financial discipline, transparency, and ethics. The developed model integrates technical literacy, internalization of cultural values, and support for simple digital applications to increase the competitiveness and sustainability of MSMEs.